Journal of Economic Sociology: Results of First 10 Years. 10 Years Have Passed, What Is Ahead? - Денис Олегович Стребков (Journal of Economic Sociology, 2010)
«Economic Sociology» celebrates its ﬁ rst 10year anniversary. It is a good reason to take all of its 50 volumes and investigate subject areas and methodological preferences of the contributors. The paper reviews journal’s history, reﬂ ects upon challenges which it met and ways it resolved them. Using the data of Russian Science Citation Index the author compares citation indexes of «Economic Sociology» with the other Russian sociological journals. Attracting relevant online statistics, the author also reveals the structure and dynamic of the journal audience over the decade, major interests and preferences of the readers.